AGAINST ALL ODDS (PERGESERAN STANDAR KECANTIKAN DALAM IKLAN KORPORAT “REAL BEAUTY” DOVE) - Tania Emyliani; Nanang Krisdinanto; Akhsaniyah Akhsaniyah (Universitas Serang Raya, 2019)
This study looked at how the matching of signs related to the shift in standard of beauty incorporate advertising